Dog Man: Lord of the Fleas #5 - Pilkey, Dav, 1966- (New York, NY : Graphix, an imprint of Scholastic, 2018)
When a new bunch of baddies arrive in town, Dog Man and his friends are called into action, but in order to save the day they need to join forces with Petey, the world's most evil cat.
"Treehouse Comix proudly presents."
Chiefly illustrations.
Keywords: Adventure and adventurers -- Fiction; Dogs -- Fiction; Police -- Fiction; Cats -- Fiction; Police -- Fiction; Cats -- Fiction; Adventure graphic novels; Humorous graphic novels; Humorous fiction; Graphic novels